Generation of ocean internal wave with vertical-slice hydrodynamic simulation. Issue 1 (February 2021) - Akhyar, M; Wafdan, R; Haditiar, Y; Ikhwan, M; Setiawan, I; Rizal, S
Abstract: The instability of the density of seawater causes the formation of internal waves in the sea. This phenomenon is difficult to observe visually but can be studied with a hydrodynamic model approach. This study investigates the internal waves caused by underwater obstructions (seamounts) and the stratified density with a two-dimensional marine hydrodynamic model. Four scenarios are simulated in studying internal waves. Two scenarios used one barrier with uniform density and stratified density (based on the Brunt Vaisala stability frequency N 2 = 5 x 10 -4 s -2 ). Meanwhile, the other two scenarios use two barriers with uniform density and stratified density (based on the Brunt Vaisala stability frequency N 2 = 5 x 10 -4 s -2 ). Based on the simulation results, it is known that the density conditions have a significant effect on the dynamics of ocean currents. In hydrodynamic simulations of one and two barriers with varying or stratified densities, current resonances and density resonances are formed underwater topography. Meanwhile, in uniform density, the currents formed the rotor, cavity, turbulence, and resonance with the underwater topography. Thus the current dynamics are stronger in the case of uniform density than in the stratified density. It has implications for differences in the mixing of suspended matter in the sea. So this study can be useful in the study of sediment transport, upwelling, the thermocline layer, energy from internal waves, and the distribution of plankton or fish larvae.